Effects of a Teacher-Training Violence Prevention Program in Jamaican Preschools on Child Behavior, Academic Achievement, and School Attendance in Grade One of Primary School: Follow up of a Cluster Randomized Trial - Baker-Henningham, Helen; Scott, Yakeisha; Francis, Taja; Walker, Susan P. (Frontiers in Psychology, 2021)
Objective: We evaluated the effect of a universal, teacher-training, violence-prevention program implemented in preschool, on high-risk children's behavior, achievement, and attendance in grade one of primary school. Methods: A cluster-randomized trial was conducted in 24 preschools in Kingston, Jamaica. Three children from each class with the highest level of teacher-reported conduct problems were recruited for evaluation of outcomes (n = 225 children). For this study, to increase power, we recruited an additional two children from each class with the next highest teacher-reported scores for conduct problems in preschool. In the final term of grade one of primary school, we assessed children's: (1) conduct problems and social skills at home and school, (2) academic achievement, language, and self-regulation skills, and (3) school attendance. Results: 214/225 (95.1%) of the children evaluated in preschool were assessed in grade one of primary school; an additional 150 children were recruited to give 364 children (181 intervention, 183 control). Significant benefits of intervention were found for child academic achievement (Effect size (ES) = 0.23, p = 0.02), oral language (ES = 0.28, p = 0.006), self-regulation (ES = 0.25, p = 0.007), and school attendance (ES = 0.30, p = 0.003). No significant benefits were found for observed conduct problems (ES = −0.13, p = 0.16), and parent-reported conduct problems (ES = 0.10, p = 0.31) and social skills (ES = −0.07, p = 0.52). Benefits to teacher-reported conduct problems and social skills were significant at p < 0.1 (ES = −0.16, p = 0.09, and ES = 0.19, p = 0.06, respectively). Conclusion: A scalable intervention involving training preschool teachers in classroom behavior management and how to promote child social-emotional competence led to positive outcomes in primary school across multiple child developmental domains for high-risk children.